Geographical variability of bacterial communities of cryoconite holes of Andean glaciers - Pittino F.; Ambrosini R.; Seeger M.; Azzoni R. S.; Diolaiuti G.; Alviz Gazitua P.; Franzetti A. (Scientific Reports, 2023)
Cryoconite holes, ponds full of melting water with sediment on the bottom, are hotspots of biodiversity on glacier surfaces and host dynamic micro-ecosystems. They have been extensively investigated in different areas of the world (e.g., the Arctic, Antarctic, Alps, and Himalaya), but so far no study has described the bacterial communities of the glaciers in the Andes, the world’s longest mountain range. In this study, we describe the bacterial communities of three small (< 2 km2) high-elevation (< 4200 m a.s.l.) glaciers of the Central Andes (Iver, East Iver and Morado glaciers) and two large (> 85 km2) glaciers of the Patagonian Andes (Exploradores and Perito Moreno glaciers) whose ablation tongues reach low altitude (< 300 m a.s.l.). Results show that the bacterial communities were generally similar to those observed in the cryoconite holes of other continents, but with few cyanobacteria (0.5% of sequences). The most abundant orders were Betaproteobacteriales, Cytophagales, Chitinophagales, Acetobacterales, Frankiales, Armatimonadales, Sphingobacteriales, Rhizobiales, Bacteroidales, Sphingomonadales, and Micrococcales. The bacterial communities differed between glaciers and both water pH and O2 concentration appeared to influence the bacterial community composition. This work thus provides the first description of the bacterial communities in cryoconite holes of South American glaciers.